On Newton-Kantorovich method for solving the nonlinear operator equation - Hameed, Hameed Husam; Eshkuvatov, Zainidin K.; Ahmedov, Anvarjon; Nik Long, Nik Mohd Asri (Hindawi Publishing Corporation, 2015)
We develop the Newton-Kantorovich method to solve the system of nonlinear Volterra integral equations where the unknown function is in logarithmic form. A new majorant function is introduced which leads to the increment of the convergence interval. The existence and uniqueness of approximate solution are proved and a numerical example is provided to show the validation of the method.